Fabry's disease: an important risk factor for stroke - Schiffmann, Raphael; Ries, Markus (The lancet, 2005)
In today's Lancet, Arndt Rolfs and colleagues describe the prevalence of Fabry's disease - (MIM 301500, α-galactosidase A mutations) in a large cohort of patients with cryptogenic - stroke.1 Fabry's disease is an under-recognised single-gene defect caused by α-galactosidase - A deficiency, which results in a failure to catabolise α-D-galactosyl glycolipid moieties. - Increased concentrations of glycolipid are a risk factor for cardiomyopathy, cardiac - conduction abnormalities, valvular defects, coronary artery disease, renal failure, - and stroke.
Gesehen am 08.05.2019